Smart handheld budget and halal tracker - Toha, Siti Fauziah; Tajuldin, Abdul A.; Abdul Rahim, Khairul Zakariya (2012)
Engineering is a discipline that not only covers numerous aspects of our everyday lives, but it also act as an integral part that govern our everyday life. This mean, without engineering, human life will be in distress. Engineers work to give practical solutions to everyday problems. An engineer not only need to apply theories, methods and tools where these are appropriate, but also to use them selectively and constantly trying to discover solutions to problem although there are no applicable theories and methods to support them. Engineers also realize that organizational and financial constraint is inevitable, thus the engineer has to look for solutions within these constraints. This paper presents the design of a smart handheld budget and tracker. The project involves three major phases which are hardware construction, software programming, and communication setup. Hardware construction requires wiring up the microcontroller as the 'brains' of the device to external input/output devices such as liquid crystal display (LCD), keypad and a radio frequency identification (RFID) reader. Software programming involves the programming of the microcontroller to interact with the earlier mentioned devices that is connected to the microcontroller to give the user choices for inputs as well as displaying it through the LCD screen. Lastly, communication setup will enable the smart handheld budget tracker interact with an external device such as personal computer and mobile phone.